Rekontekstualisasi Teks Islam Klasik: Kajian Sosiopragmatik atas Penggunaan Pegon dalam Pembelajaran Kitab Kuning - Abdan Syakuro, M. Niqo; Ni Made , Melani Cahyanthi Putri; Ni Putu, Ratna Purnama Dewi; Damayanti, Elfina; Shandy Dwidya Sistha, Tjokorda Istri (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2026)
Pegon plays a strategic role in kitab kuning instruction in pesantren as a medium that bridges classical Islamic texts with students’ sociocultural contexts. Pegon functions as a localized linguistic medium that facilitates the recontextualization of classical Islamic texts within the sociocultural environment of pesantren education. Using a qualitative approach, data were collected through classroom observations, interviews, and documentation, and analyzed through a sociopragmatic framework focusing on speech acts, interactional patterns, and contextual meaning. The findings indicate that Pegon is not merely a transliteration tool but an integral pedagogical strategy that mediates meaning, reinforces teacher authority, and supports students’ comprehension of complex texts. Classroom interaction is characterized by the predominance of directive speech acts and receptive student responses, reflecting culturally embedded pedagogical norms. This study contributes to sociopragmatic and linguistic education research by highlighting the pedagogical significance of local language practices in religious learning contexts.